On the Issue of Systematization of Modern Terminology of Advertising and Public Relations - A. D. Krivonosov (Дискурс, 2023)
Introduction. The dynamic development and diversification of the modern public sphere, especially in the conditions of total digitalization and mediatization, requires modern scientific reflection.The article proposes the principles of classification of the system of terms of advertising and public relations. The purpose of the article is to demonstrate the operationality of using a nested method of lexicographic fixation of advertising and public relations terms based on the classical model of G. Lasswell's communication of concepts.Methodology and sources. The problems of lexicography of terms of the communication sphere (journalism, applied communications, media communications) have their own scientific reflection. The article proposes a model of a modern dictionary of advertising and public relations, where the components of the G. Lasswell model form the basis of the nest principle.Results and discussion. The article suggests the main nests (conceptual and terminological fields) of the dictionary of advertising and public relations: basic; communication subjects; communication objects; communication tools (traditional and new); communication technologies; communication results; communication product. The analysis of the composition of dictionary nests made it possible to identify dichotomies as classifying features of dictionary terms: according to the original scientific discipline; according to the use in the thematic field; according to etymology; according to the writing of borrowings; according to the structure; according to the productivity of the word-formation model.Conclusion. Description and classification of the terminology of advertising and public relations revealed a number of problems of describing the terms of new social practices and scientific disciplines: the boundaries of the subject of research; the principles of selection of sources, the specifics of lexicographic processing (from the dictionary to the glossary and dictionary). The work on the dictionary may in the future provide material for discussing a number of linguistic tasks proper.